1991
DOI: 10.1017/s0031182000059916
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofPlagiorhynchus cylindraceus(Acanthocephala) on the energy metabolism of adult starlings,sturnus vulgaris

Abstract: Although the relationship between intestinal parasitism, the ingestion and use of energy, and host survival is expected, little work has been done to outline the effect of such organisms upon their host's nutritional requirements in an ecological context. This study is the first to demonstrate that an intestinal helminth previously reported to be of little or no histopathological consequence, Plagiorhynchus cylindraceus, has a significant detrimental impact upon the flow of food energy through a definitive hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 36 publications
2
50
1
Order By: Relevance
“…Several studies reported the effect on body mass and physiology of sub-lethal helminth parasites on vertebrate hosts (Connors and Nickol 1991;Hammond 2000, 2001). These parasites can reside in their host for weeks, months or years causing a chronic infection.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the effect on body mass and physiology of sub-lethal helminth parasites on vertebrate hosts (Connors and Nickol 1991;Hammond 2000, 2001). These parasites can reside in their host for weeks, months or years causing a chronic infection.…”
Section: Introductionmentioning
confidence: 99%
“…Parasitic infections can impair hosts' metabolic capacities, and these effects may be exaggerated in stressful conditions (for example, see Schall et al 1982;de Lope et al 1993). To date, there have been relatively few studies of the consequences of parasitic infection on the metabolic capacities of wild vertebrates (fish, Walkey and Meakins 1970;Lester 1971;Lemly and Esch 1984;Coleman 1993;amphibians, Goater et al 1993;lizards, Schall et al 1982;Christian and Bedford 1995;Oppliger et al 1996;and birds, Hayworth et al 1987;Connors and Nickol 1991;Booth et al 1993;Chappell et al 1996) and only a single study of wild mammals (Munger and Karasov 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be difficult in field studies to detect patholo gical impact, as affected individuals should be rapidly eliminated by predation (Holmes, 1983). Moreover, the effect of the parasite (if there is one) may not be obvious on the biological indices studied at the level of the population even if it has been previously demons trated that host energy metabolism could be affected by acanthocephalans (Connors & Nickol, 1991). On the one hand, sex hormone secretion for gonad maturation in females after maturity can play an influential role in the regulation of the immune res ponse and therefore favor parasitism (Alexander & Stimson, 1988;M0ller, 1993).…”
Section: O Ur Results Show a Selectively Different Effect Ofmentioning
confidence: 99%